(De)structuring teacher careers at Brazilian federal universities - Rocha, Francilene Macedo; Melo, Savana Diniz Gomes; Silva, Rafaela Campos Duarte (Education Policy Analysis Archives, 2022)
The article is the result of research aimed at the study of higher education in Brazil, specifically the careers of professors at federal universities, in order to identify and analyze the meaning of the changes processed in the period from 2012 to 2018. The starting point of the study is the year 2012, due to the outbreak of a major national strike by the professors of these institutions, in which one of the demands was a single career. This strike lasted for 120 days and its outcome was conflicted with the approval of a new teaching career plan contrary to the claims of the category. The study is based on documentary research with analysis of legislation, official documents and publications of the National Union of Teachers of Higher Education Institutions. The study shows the disruption of the teaching career at federal universities throughout the 1990s and its deepening as of 2012, in line with the business reform of higher education undertaken in the country during this period. Further, this situation is likely to worsen with the measures underway, which aim to consolidate the new model of university managed by social organizations.